Teacher-Student Relationship Quality and School Safety as Predictors of Sense of School Belonging in High Schools - Erol, Yusuf Celal; Köse, Nihat (Marmara Üniversitesi, 2026)
The aim of this study is to examine the relationships between the quality of teacher-student relationships, the perception of school safety, and the sense of school belonging in high schools. Furthermore, if a relationship exists among these variables, the study seeks to determine the extent to which high school students' perceptions of teacher-student relationship quality and school safety predict their sense of school belonging. This study was conducted using a relational survey model, and the sample consists of high school students from Turkiye who participated in the PISA 2022 study. In PISA 2022, a total of 196 schools and 7,250 students [3,561 female students (49.1%9 and 3,689 male students (50.9%)] participated from Turkıye. After eliminating missing data, analyses were conducted on a dataset comprising data from 7,206 high school students. The data were collected using the Teacher-Student Relationship Quality Questionnaire, the School Safety Questionnaire, and the Sense of School Belonging Questionnaire. According to the findings of the study, high school students perceive the quality of teacher-student relationships in their schools positively, generally feel safe at school, and exhibit a sense of school belonging. Additionally, significant positive correlations were found between the quality of teacher-student relationships and both students' sense of school belonging and their perception of school safety. The findings indicate that 15.4% of the variance in students’ sense of school belonging can be explained by the quality of teacher-student relationships and perceptions of school safety. To foster students' sense of school belonging or enhance their existing level of belongingness, efforts should be made to improve the quality of teacher-student relationships and to implement measures that contribute to school safety, ensuring that schools are perceived as safer environments by students.

Bu araştırmanın amacı, liselerde okula ait olma hissi, öğretmen-öğrenci ilişkilerinin kalitesi ve okul güvenliği algısı arasındaki ilişkilerin belirlenmesi ve aralarında ilişki varsa, lise öğrencilerinin öğretmen-öğrenci ilişkilerinin kalitesi ve okul güvenliğine yönelik algılarının, okula aidiyet duygusunu ne düzeyde yordadığının ortaya konmasıdır. İlişkisel tarama modelinde gerçekleştirilen bu çalışmanın evrenini Türkiye’deki liseler, örneklemini ise, PISA 2022 araştırmasına Türkiye’den katılan lise öğrencileri oluşturmaktadır. PISA 2022 araştırmasına Türkiye'den 196 okul ve 7250 öğrenci [3561 kız öğrenci (%49,1); 3689 erkek öğrenci (%50,9)] katılım sağlamıştır. Kayıp veriler ayıklandıktan sonra toplam 7206 lise öğrencisinden Öğrenci-Öğretmen İlişkilerinin Kalitesi Anketi, Okul Güvenliği Anketi ve Okula Aidiyet Duygusu Anketi ile elde edilen verileri içeren veri seti üzerinde analizler yapılmıştır. Çalışma sonuçlarına göre, lise öğrencileri, öğrenim gördükleri okullardaki öğretmen-öğrenci ilişkilerinin kalitesini olumlu algıladıkları, genel olarak okulda kendilerini güvende hissettikleri ve öğrencilerin okula ait olma duygusuna sahip oldukları görülmektedir. Ayrıca, öğretmen-öğrenci ilişkisinin kalitesi ile lise öğrencilerinin okula ait olma duygusu ve okul güvenliği algıları arasında pozitif yönlü anlamlı ilişkiler bulunmaktadır. Lise öğrencilerinin okula ait olma duygusunun %15,4’ünün, öğretmen öğrenci ilişkilerinin kalitesi ve okul güvenliğinden kaynaklandığı sonucuna ulaşılmıştır. Öğrencilerin okula ait olma hissi taşımaları veya var olan ait olma hissi düzeylerinin arttırılması için, öğretmenler ve öğrenciler arasındaki ilişkilerin kalitesinin yükseltilmesi ve okulların öğrenciler tarafından daha güvenli bir olarak algılanmaları için okul güvenliğine katkı sağlayacak çalışmalar yapılması gerekmektedir.
Liselerde Okula Ait Olma Hissinin Yordayıcıları Olarak Öğretmen-Öğrenci İlişkisinin Kalitesi ve Okul Güvenliği
Keywords: Education Management; Eğitim Yönetimi